Glucose tolerance and cardiovascular risk biomarkers in non-diabetic non-obese obstructive sleep apnea patients: Effects of long-term continuous positive airway pressure. (March 2016) - Monneret, D.; Tamisier, R.; Ducros, V.; Faure, P.; Halimi, S.; Baguet, J.P.; Lévy, P.; Pépin, J.L.; Borel, A.L.
Abstract: Background: Insulin resistance, glucose dyshomeostasis and oxidative stress are associated to the cardiovascular consequences of obstructive sleep apnea (OSA). The effects of a long-term continuous positive airway pressure (LT-CPAP) treatment on such mechanisms still remain conflicting. Objective: To investigate the effect of LT-CPAP on glucose tolerance, insulin sensitivity, oxidative stress and cardiovascular biomarkers in non-obese non-diabetic OSA patients. Patients & methods: Twenty-eight apneic, otherwise healthy, men suffering from OSA (mean age = 48.9 ± 9.4 years; apnea-hypopnea index = 41.1 ± 16.1 events/h; BMI = 26.6 ± 2.8 kg/m 2 ; fasting glucose = 4.98 ± 0.37 mmol/L) were evaluated before and after LT-CPAP by an oral glucose tolerance test (OGTT), measuring plasma glucose, insulin and proinsulin. Glycated hemoglobin, homeostasis model assessment resistance insulin, blood lipids, oxidative stress, homocysteine and NT-pro-brain natriuretic peptide (NT-proBNP) were also measured. Results: LT-CPAP treatment lasted 13.9 ± 6.5 months. At baseline, the time spent at SaO2 <90%, minimal and mean SaO2 were associated with insulin area under the curve during OGTT (r = 0.448, P = 0.011; r = −0.382; P = 0.047 and r = −0.424; P = 0.028, respectively) and most other glucose/insulin homeostasis biomarkers, as well as with homocysteine (r = 0.531, P = 0.006; r = −0.487; P = 0.011 and r = −0.409; P = 0.034, respectively). LT-CPAP had no effect on all the OGTT-related measurements, but increased plasma total antioxidant status (+7.74%; P = 0.035) in a duration-dependent manner (r = 0.607; P < 0.001), and decreased both homocysteine (−15.2%; P = 0.002) and NT-proBNP levels (−39.3%; P = 0.002). Conclusions: In non-obese non-diabetic OSA patients, nocturnal oxygen desaturation is strongly associated to insulin resistance. LT-CPAP does not improve glucose homeostasis nor insulin sensitivity but has a favorable effect on antioxidant capacity and cardiovascular risk biomarkers. Highlights: Insulin resistance and raised oxidative stress are linked to obstructive sleep apnea. These metabolic disorders lead to the deleterious cardiovascular consequences of OSA. The effects of long-term CPAP in non-obese non-diabetic OSA patients are studied. Long-term CPAP does not improve glucose homeostasis nor insulin sensitivity. But it has a favorable effect on antioxidant capacity and cardiovascular biomarkers.